Maternal Health Outcomes in a Somalia Post-war Context: a PhD thesis analyzing trends towards universal health coverage - Aden, Jamila (Somali Health Action Journal, 2022)
Abstract Somalia has one of the highest maternal mortality ratios in the world and an inequitable distribution of maternal health outcomes and service utilisation. Like other developing countries, Somalia has adopted the global policy goal of attaining universal health coverage of health services and improved health outcomes across all populations. Although United Nations agencies track the progress towards achieving universal health coverage as part of health targets for achieving the Sustainable Development Goals, empirical case studies are rarely documented, especially in developing countries and even more so in post-war contexts such as Somalia. Literature shows the overall progress towards globally agreed-upon targets for maternal health lagging in war-affected countries, with persistent socioeconomic gradients in health outcomes. However, little is known about the mechanisms through which the social determinants of health impact on the distribution of maternal health outcomes. The aim of this study is to examine the mechanisms through which social determinants contribute to inequities in maternal health outcomes in Somalia. Specifically, the study will analyse the policy context and progress towards achieving universal health coverage of maternal health services in Somalia; analyse trends in maternal health outcomes and inequities in Somalia; and examine the mechanisms through which social determinants contribute to inequities in maternal health outcomes. A mixed-methods case study design will be adopted, employing both qualitative and quantitative approaches to data collection and analysis. The findings of this PhD research will contribute to the evidence base on pathways for achieving universal health coverage of maternal health outcomes in post-war countries like Somalia. This will facilitate development of effective health care policies and those addressing the social determinants, which if implemented will improve maternal health outcomes in Somalia and mark progress towards achieving the goal of universal maternal health coverage.